KEPADATAN POPULASI WALANG SANGIT (Leptocorisa acuta Thunb) (Hemiptera;Alydidae) PADA TANAMAN PADI DI KENAGARIAN KOTO NAN TIGO KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Dewidna, Sefria; Jasmi, Jasmi; Indriati, Gustina (STKIP PGRI Sumbar, 2013)
ABSTRACTOne of insect pests that attack the rice plant is Leptocorisa acuta Thunb ( ladybugs stink ) . Local people know Leptocorisa as pianggang acuta Thunb . This pest attacks the rice in a productive phase by sucking fluids rice fruit . These pests can cause grain to be empty will result in a decrease in yield . In connection with that have done research on population density Leptocorisa acuta Thunb on rice plants from 25 until May 26, 2013 . Sampling was done at Koto Nan Tigo Kenagarian district Batang Kapas South Coastal District with a descriptive surve y method and the direct collection of the Leptocorisa acuta Thunb that existed at the study site by way sweepan ( sweeping ) . Collection by using systematic random sampling technique sampling . Decision made for 2 days in a row 2 times ( morning and afternoon ) on flowering phase and phase cook milk . Decision made at 15 points in each phase . The results were obtained an average population density is 33.93 Leptocorisa acuta perpengambilan tail . In this case acuta Thunb Leptocorisa population had crossed the threshold .